Use of strain sonoelastography in differentiation of focal testicular lesions - Mohamed Samir Shaaban (The Egyptian Journal of Radiology and Nuclear Medicine, 2017)
Purpose: We aimed to assess potential role of strain sonoelastography in diagnosing focal testicular lesions. Patient & methods: 21 patients with 23 focal testicular lesions were subjected to sonoelastography. Compression was performed manually by the transducer upon the testis and monitored on the compression graph on the machine. Diagnosis was reached either by surgical resection, or follow-up. Result: 23 focal testicular lesions were included. 10 lesions were in the right and 9 in the left, and 2 lesions are bilateral. Cases included 7 focal orchitis (30.5%), two hematomas (8.7%), 7 scar tissue (30.5%), 4 seminomas (17.4%), one choriocrcinoma (4.3%), one epidermoid cyst (4.3%), and one hydatid cyst (4.3%). On strain Sonoelastography; all four seminomas and 7 scars were of low strain, also the epidermoid cyst and the two hematomas were hard, while the 7 cases of focal orchitis showed high strain. The cases of choriocarcinoma and the hydatid cyst showed mixed strain patterns. Statistical analyses showed a sensitivity of 100% in identifying neoplastic lesions, with a specificity of 40%, a negative predictive value of 100%, and a positive predictive value of 37.5%. Conclusion: Strain Sonoelastography is useful adjunct method to differentiate benign from malignant focal testicular lesions.